2011
DOI: 10.1177/0194599811399240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH Monitoring on Laryngopharyngeal Reflux Treatment

Abstract: Among our patient population, treatment of LPR based on pH monitoring resulted in greater compliance, as well as greater symptom improvement, compared with empirical therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
1
27
0
1
Order By: Relevance
“…In our study, based on its current thresholds it cannot serve as a stand-alone diagnostic tool to reliably identify symptomatic patients with LPR. Smaller single center studies have suggested that oropharyngeal pH testing may have a role in predicting response to anti-reflux therapy 15, 16 and larger multicenter studies to evaluate the oropharyngeal pH probe's role in predicting treatment outcomes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, based on its current thresholds it cannot serve as a stand-alone diagnostic tool to reliably identify symptomatic patients with LPR. Smaller single center studies have suggested that oropharyngeal pH testing may have a role in predicting response to anti-reflux therapy 15, 16 and larger multicenter studies to evaluate the oropharyngeal pH probe's role in predicting treatment outcomes are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective case control study of 170 patients with LPR symptoms, Friedman et al reported that PPI therapy based on a positive RYAN score compared to empiric PPI therapy resulted in significantly increased symptom response and compliance to therapy; however, in both the control and case groups the RSI significantly decreased following treatment, with mean post-treatment RSIs less than 13. 37 A prospective study of 22 patients with LPR symptoms reported a 59% response rate to PPI therapy, and described that oropharyngeal pH testing has a 69% sensitivity and 100% specificity for predicting PPI response. However, response was defined as at least a 5-point decrease in RSI; derivation of this 5-point decrease threshold is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Rarer but more serious manifestations or complications associated with LPRD include laryngospasm and laryngeal cancer (14,18). Several tests have been used to diagnose LPRD and these include: Reflux Symptom Index (RSI), Reflux Finding Score (RFS), Double probe pH monitoring, Pepsin (sputum) as a marker of LPR, Sensory testing; Laryngopharyngeal sensory descrimination testing (FEESST), Esophagoscopy, Barium esophagography and Bernstein acid perfusion (19)(20)(21)(22)(23). The reflux symptoms Index was described by Belfaski as a compilation of nine reflux related laryngeopharyngeal symptoms.…”
Section: Discussionmentioning
confidence: 99%